À propos de la découverte d’un dictionnaire inédit du xviiie siècle - Joan Thomas (Lengas)
This dictionary of the 18th century is a real linguistic treasure of more than 2000 pages and 34000 entries. Anonymous, never published nor copied by the Occitan lexicographers, this work which is rigorously built, gives us to read the everyday life in Provence and in Languedoc before the Revolution. This work overtakes that of Boissier de Sauvages. It’s a dictionary between two languages in which the illustrations of the definitions are made by proverbs and by examples taken in the literature, which offer a new vision of the literary history of the 18th century.This dictionary is now available on http://tolosana.univ-toulouse.fr/notice/165803770